SHAPE CONTROL AND DAMAGE IDENTIFICATION OF PIEZOELECTRIC SMART BEAMS USING FINITE ELEMENT MODELLING AND GENETIC OPTIMIZATION - HADJIGEORGIOU, E. P.; MASSALAS, C. V.; STAVROULAKIS, G. E. (Mathematical Methods In Scattering Theory And Biomedical Engineering, 2006)
This paper deals with the shape control of beams, using piezoelectric patch actuators that are surface bonded onto beams to provide the control forces. The mathematical formulation of the model is based on the shear deformation beam theory and the linear theory of piezoelectricity. The numerical solution of the model is based on the development of superconvergent (locking-free) finite elements. For the shape control of a cantilever beam, the optimal voltages of the piezo-actuators are determined using a genetic optimization procedure. Finally, a simplified related damage identification problem is formulated and solved using static data and genetic optimization.